Composition of the Volatile Oils of Anthemis coelopoda var. coelopoda from Turkey ? - Dogan, Gülden; Demirpolat, Azize; Bagcı, Eyüp (Hacettepe Üniversitesi, 2015)
In this study, hydro distilled essential oils derived from the aerial parts of Anthemis coelopoda var. coelo- poda Asteraceae grown in Turkey were analysed by GC and GC-MS system. Fifty seven components were identified representing 90.7% of the oils. It was determined that Anthemis coelopoda var. coelopoda essential oil contained b-caryophyllene 21.8% , nerolidol 10.8% , azulene 9.5% , borneol 5.5% , linalool 4.3% and cyclopentadecane 4.2% as major compounds. Essential oil analysis of the Anthemis coelopoda var. coelopoda has shown that it has b-caryophyllene/nerolidol and azulene chemotype.

B u çalışmada Türkiye’de yetişen Anthemis coelopoda var. coelopoda türünün su damıtma yöntemi ile toprak üstü kısımlarından elde edilen uçucu yağları GC ve GC-MS’de analiz edilmiştir. Toplam yağın %90.7’sinde 57 bileşen belirlenmiştir. Anthemis coelopoda var. coelopoda’nın uçucu yağının içerdiği bu bileşenlerden b-karyofillen %21.8 , nerolidol 10.8 % , azulen %9.5 , borneol %5.5 , linalool %4.3 ve siklopentadekan %4.2 büyük bileşenlerdir. Uçucu yağ çalışmaları Anthemis coelopoda var. coelopoda için b-karyofillen/nerolidol ve azulen kemotip olduğunu göstermiştir
Türkiye’den Anthemis coelopoda var. coelopoda’nın Uçucu Yağ Bileşimi